Tool Life Investigation of the Thread Making Tools - Monkova, Katarina; Monka, Peter; Jurko, Jozef; Bílek, Ondřej; Habel, Jacek (Manufacturing Technology Journal, 2018)
The article deals with an experimental investigation tool life of the thread making tools. During long-time tests, the uncoated taps for M12 threads making were used. They were produced from high speed steel with cone type C. Three helix angles ω = 0°, 15° and 35° of taps have been investigated at the cutting speeds of 10 mmin-1 (within the first experimental phase) and 20, 30, 40 mmin-1 (during the second phase). The holes for threads making were pre-drilled into workpieces that were bars (with a cross-section of 30 x 60 mm). They were produced from C45 steel that is a standard material used at long-term tests of tool durability. Microhardness of the workpiece bars was checked within preliminary tests as well as a rank angle of tools to be ensured the same conditions of experiments. The changes in a size of the M12 thread outside the tolerance field 6H, the visible changes in tool wear and the brittle fractures of the tools have been selected as the criteria for tool life evaluation. Achieved results were statistically processed and the dependencies of thread length (m) and tool life (min) respectively on the cutting speed were plotted. The types of tool wear have been also analysed at individual cutting speeds.
Keywords: tool life; thread; tap; experiments; helix angle; tool wear